Boswellia serrata - Tironi de Castilho, Ana Laura [UNESP]; de Liori Teixeira, Leonardo [UNESP]; Costa Lima, Victor Antonio [UNESP]; Pesse, Vanessa Bonassa [UNESP]; Rozza, Ariane Leite [UNESP] (Elsevier, 2022)
Natural products we usually fed aid in preventing and treating various diseases, besides their nutritional functions. Recent clinical and preclinical studies have shown that consuming herbs and spices triggers beneficial biological effects. Boswellia serrata is a tree found mainly in dry areas in India, and traditional Arab, Ayurvedic, and Chinese medicine use its oleogum resin for medicinal purposes. Furthermore, there are several studies about its role as a nutraceutical and functional food. So, here we reviewed the beneficial effects of B. serrata on nutrition, as it presents antiinflammatory, anticancer, antidiabetic, and antioxidant properties, among others. The highlighting of B. serrata beneficial effects could offer a helpful direction to future studies and the development of a phytomedicine for the prevention and treatment of health conditions.
Keywords: AKBA; Boswellia serrata; Gum resin extract; Oleoresin; Oxidative stress; Pentacyclic triterpenic acids